Investigation of protein-ligand complexes by ligand-based NMR methods. (May 2021) - Di Carluccio, Cristina; Forgione, Maria Concetta; Martini, Silvia; Berti, Francesco; Molinaro, Antonio; Marchetti, Roberta; Silipo, Alba
Abstract: Molecular recognition is at the base of all biological events and its knowledge at atomic level is pivotal in the development of new drug design approaches. NMR spectroscopy is one of the most widely used technique to detect and characterize transient ligand-receptor interactions in solution. In particular, ligand-based NMR approaches, including NOE-based NMR techniques, diffusion experiments and relaxation methods, are excellent tools to investigate how ligands interact with their receptors. Here we describe the key structural information that can be achieved on binding processes thanks to the combined used of advanced NMR and computational methods. Saturation Transfer Difference NMR (STD-NMR), WaterLOGSY, diffusion- and relaxation-based experiments, together with tr-NOE techniques allow, indeed, to investigate the ligand behavior when bound to a receptor, determining, among others, the epitope map of the ligand and its bioactive conformation. The combination of these NMR techniques with computational methods, including docking, molecular dynamics and CORCEMA-ST analysis, permits to define and validate an accurate 3D model of protein-ligand complexes. Graphical abstract: Image 1 Highlights: Protein-ligand interactions are involved in several biological events and diseases. Molecular studies of protein-ligand complexes promote new therapeutic strategies. Ligand-based NMR methods to investigate ligand binding to protein are here described.